Exploring the Accessibility and Facility in Railway Station Used by Persons With Disabilities: an Experience From Kebayoran Railway Station, Jakarta - Tamba, Jefri (Indonesian Journal of Disability Studies, 2018)
This paper discusses accessibility at Kebayoran Railway Station's facility for persons with disabilities. Kebayoran Railway Station as one of Railway Stations on Tanah Abang, Rangkasbitung railway track, which has been revitalized in 2016. A descriptive approach used in this research and found that currently, Kebayoran Railway Station has been more accessible for persons with disabilities. The results indicate that some disability's facilities consist of: (a) toilet; (b) safe pick-up and set-down facility; (c) facility for persons with disability; (d) other facility (tactile paving). The Minister of Transportation Decree 47 Year 2014 regarding Minimum Service Standard for Train Public Transportation at Kebayoran Railway Station facilities is one of the guidelines for PT. KAI Commuter Jabodetabek in building facilities in the station. In this case, Kebayoran Railway Station has implemented the Minister of Transportation's Decree and makes it easy for some persons with disabilities to use the facilities at the railway station.